বাংলা ভাষায় আরবী ফারসী তুর্কী হিন্দী উর্দু শব্দের অভিধান - হক, কাজী রফিকুল; বাংলা একাডেমী (ঢাকা : বাংলা একাডেমী, 2004)
Dictionary of Arabic, Persian, Turkish, Hindi, and Urdu words that have become part of the Bengali language.
Bengali, Arabic, Persian, Turkish, Hindi, and Urdu.
Keywords: Bengali language -- Foreign words and phrases -- Dictionaries